On a singular integral equation including a set of multivariate polynomials suggested by Laguerre polynomials - Özarslan, Mehmet Ali (Elsevier, 2014)
In this paper, we introduce the class of polynomials Zn1,…,nj(α)(x1,…,xj;ρ1,…,ρj) suggested by the multivariate Laguerre polynomials. We give Schläfli’s contour integral representation and calculate the fractional order integral of these polynomials. Furthermore, we obtain linear, multilinear and mixed multilateral generating functions for them. Finally, we construct a singular integral equation with Zn1,…,nj(α)(x1,…,xj;ρ1,…,ρj) in the kernel and obtain the solution in terms of multivariate analogue of the Mittag–Leffler functions.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: MATHEMATICS, APPLIED, FAMILIES, KONHAUSER SETS, Generating functions; Mittag-Leffler function, Contour integral representation, Laplace transform; Multivariate Laguerre polynomials, Singular integral equation; Fractional integrals and derivatives, BIORTHOGONAL POLYNOMIALS